Selenium is an essential trace nutrient for growth of WI-38 diploid human fibroblasts. - McKeehan, W L (1976)
The trace element selenium is essential for clonal growth of diploid fibroblasts from human fetal lung (WI-38) in media containing small amounts of serum protein. Maximum growth stimulation is obtained when 30 nM neutralized selenious acid is added to a synthetic medium containing 1.5 mg/ml of dialyzed fetal bovine serum protein (equivalent to a 3% serum concentration). Serum appears to be a source of selenium in most culture media, since higher concentrations of serum protein or whole serum mask the selenium requirement of WI-38 cells. Selenium is also required by a Chinese hamster cell line that can be grown in a protein-free synthetic culture medium.